Eating disorders - Abraham, Suzanne (Oxford University Press, 2001)
The eating disorders - anorexia nervosa, bulimia nervosa, and obesity -affect many thousands of people each year, particularly young women, though men as well. This comprehensive guide considers why eating disorders occur, and then looks at each in turn, describing the eating behaviours, diagnosis, and treatments available. This new edition has been fully revised and updated. Included is a new chapter explaining and providing advice on the problems someone with an eating disorder may face while pregnant, and after giving birth. An additional chapter looks at the problems that the family or friends of someone with an eating disorder may face, accepting that there is a problem, the feeling that somehow they are responsible, helplessness, and how they can cope and provide support and help for the sufferer Sympathetically and clearly written, the book provides an authoritative resource on eating disorders and how to treat them, one that will prove valuable for sufferers and their families